Participação social no processo legislativo federal: um estudo da Comissão de Legislação Participativa (CLP), da Comissão de Direitos Humanos e Legislação Participativa (CDH) e da iniciativa popular de lei - Augusto, Luís Gustavo Henrique (2015)
This research aims to determine whether the Participative Legislation Committees of the Câmara dos Deputados and the Senado Federal facilitated social participation in legislative process comparing to the traditional institute of the Law Popular Initiative. To provide the basis that guide the investigation of these mechanisms of participation was undertaken a dogmatic study of the federal legislative process; investigation of how social participation is prescribed in the Constitution and Bylaws of the Legislative Houses, aiming to see how political participation is implemented in legislative procedures; besides the study of the relationship between representation and participation. For this were used the literature review, document analysis, data collection, case studies and interviews. According to the study the Committees facilitated social participation in the legislative process with regard to the disposal of part of the formal requirements that hamper the participation via Popular Initiative; besides expanding the types of legislative proposals that society can provide. However, these new mechanisms reproduced other limitations that the Popular Initiative has, in addition to disregard, in their structure, essential elements to achieve a legislative process effectively participatory, which are covered by the traditional institute, allowing then to say that the Committees are institutional innovations limited front of the institute of Popular Initiative.